1999
DOI: 10.1007/s002770050468
|View full text |Cite
|
Sign up to set email alerts
|

Digital clubbing in a patient with progressive mantle cell lymphoma

Abstract: Digital clubbing with or without hypertrophic osteoarthropathy may occur in a variety of neoplastic diseases. We present the first description of digital clubbing in a patient with progressive mantle cell lymphoma, in the absence of any other apparent etiology. We suggest that clubbing might be a paraneoplastic manifestation in mantle cell lymphoma. The literature on digital clubbing in hematological neoplasms is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Tumor tissue produces a releasing factor (vascular endothelial growth factor) for stimulating the digital clubbing and HOA process [1,22,26]. HOA involvement can be preceded by isolated digital clubbing [27]. Some studies reported that raised levels of prostaglandin E2 could be associated with digital clubbing and HOA in lung cancer patients [28].…”
Section: Sridhar Et Al Reported 111 Patients With Lung Cancer Of Whom 32 Patients Had Digital Clubbing As the Clinical Presentation (29%)mentioning
confidence: 99%
“…Tumor tissue produces a releasing factor (vascular endothelial growth factor) for stimulating the digital clubbing and HOA process [1,22,26]. HOA involvement can be preceded by isolated digital clubbing [27]. Some studies reported that raised levels of prostaglandin E2 could be associated with digital clubbing and HOA in lung cancer patients [28].…”
Section: Sridhar Et Al Reported 111 Patients With Lung Cancer Of Whom 32 Patients Had Digital Clubbing As the Clinical Presentation (29%)mentioning
confidence: 99%